Peningkatan efektivitas pemasaran pada usaha retail melalui digitalisasi katalog dengan microsite - Arifiyani, Ferent Cindy; Pramaditya, Himawan (Universitas Merdeka Malang, 2023)
Changes in business systems are becoming increasingly important in the current technological era. The phenomenon of business digitization can affect many aspects, including marketing aspects in retail businesses that sell electronic products. In this case, it is necessary to modernize the sales system which still uses conventional business models by providing printed catalogs to customers. Print catalogs have limitations in the number of products that can be displayed and are less attractive to customers. This study aims to develop a sales system for electronic product retail businesses by digitizing catalogs using the microsite feature. This catalog digitization system is applied to e-commerce as an online catalog, while the microsite is used to support increased sales. In this study, the survey method was conducted on 80 respondents who were customers or prospective customers of the retail business which was the object of research. The results of the study show that digitizing catalogs with microsites can effectively increase store attractiveness, so that the number of visits continues to increase. In addition, the system built also makes connections between e-commerce and social media so that they can provide the same information, thereby forming consumer relations that meet consumer needs.